LA VECINDAD CON ESTADOS UNIDOS: INTERÉS NACIONAL Y OPINIÓN PÚBLICA - De Olden, Laura (El Colegio de México A.C., 2015)
This paper analyzes the individual factors that affect the cost-benefit perceptions of having the United States as a neighbor in Mexican public opinion. A statistical multivariate linear regression model is constructed. Mexicans posses well-founded, differentiated, and rational opinions that display patterns of conceptual coherence. The cost-benefit evaluations associated with having the United States as a neighbor depend less on the demographic characteristics of Mexicans and more on the fundamental values and predispositions associated with national identity, including the principles of internationalism, economic liberalism, sovereignty and perceptions of the relative vulnerability of Mexico visà-vis the United States.